Long Noncoding RNA ENSG00000254693 Promotes Diabetic Kidney Disease via Interacting with HuR - Qun Yu; Jiangong Lin; Qiqi Ma; Yanmei Li; Qianhui Wang; Huimin Chen; Yue Liu; Bing Liu (Journal of Diabetes Research)
Diabetic kidney disease (DKD) is one of the most common complications of diabetes mellitus (DM), without suitable therapies, causing end-stage renal diseases (ESRDs) ultimately. Moreover, there is increasing evidence demonstrating that long noncoding RNAs (lncRNAs) play crucial roles in the development of DKD. Our RNA sequencing data revealed a large group of differentially expressed lncRNAs in renal tissues of DKD, of which lncRNA ENSG00000254693 (lncRNA 254693 for short) changed drastically. In this study, we found that the expression of lncRNA 254693 was increased in both DKD patients and high-glucose-induced human podocytes. 5′/3′RACE and Northern blot assays were used to find the full length of lncRNA ENSG00000254693 which is 558 nucleotides and nonisoform that existed in human podocyte. Downregulation of lncRNA 254693 remarkably reversed the elevation of inflammation, apoptosis, and podocyte injury caused by high glucose. Then, we did bioinformatics analysis via RBPDB and found that lncRNA 254693 can combine with HuR, a RNA binding protein. Meanwhile, immunofluorescence and in situ hybridization double staining was used to prove the existence of colocalization between them. Intriguingly, lncRNA 254693 knockdown decreased HuR levels, while HuR knockdown also decreased the level of lncRNA 254693 and its stability. After this, RNA immunoprecipitation assay results confirmed the binding association between them again. In addition, we found that HuR was increased in high glucose-induced podocytes, and the silence of HuR could alleviate podocyte injury, inflammation, and apoptosis. These results together suggested a novel feedback regulation between lncRNA 254693 and HuR which could involve in podocyte injury and may serve as a predicted target for DKD therapies.